Acute Toxicity of Synthetic Pyretroid Cypermethrin to the Young Rainbow Trout (Oncorhychus mykiss Walbaum, 1792) - Kuecuekbay, F. Z.; Doeruecue, M.; Yazlak, H. (Asian Journal of Chemistry, 2009)
The acute toxicity of synthetic pyrethroid cypermethrin contaminating aquatic ecosystems as a potential toxic pollutant was examined in this study. Young rainbow trout (Oncorhynchus mykiss), 50-60 g in weight and 10-15 cm in length was used for the bioassay experiments. Cumulative mortality and 24,48, 72 and 96 h LC50 values were determined for young rainbow trout. The behaviour of young rainbow trout at each cypermethrin concentration was also observed. Data obtained from this study were evaluated by use of probit analysis statistical method, The 24, 48, 72 and 96 h LC50 values (95 % confidence limit) for young rainbow trout were estimated to be 68.492 (35.704-101.280), 55.941 (27.616-84.266),47.597 (43.344-51.715) and 41.786 (39.823-43.371) mu g/L, respectively.
Keywords: Acute toxicity; Bioassay; Cypermethrin; Oncorhynchus mykiss; Behavioural changes